2020
DOI: 10.1210/jendso/bvaa046.540
|View full text |Cite
|
Sign up to set email alerts
|

MON-638 The WBC Differential in Relation to DKA Severity

Abstract: BACKGROUND: Diabetic ketoacidosis (DKA) is well-known to be associated with increased levels of inflammatory markers including cytokines. Interestingly, an elevated white blood count (WBC) has been associated with a higher prevalence of acute and chronic diabetes metabolic complications, including DKA, and micro- and macrovascular complications (Tong et al., 2004; Xu et al., 2013). However, very few studies have looked at the relationship between WBC differential and the severity of DKA. For instance, a study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This simple ratio, which combines the predictive power of both increased neutrophil and decreased lymphocyte counts, has the advantage of being ubiquitous, cost effective, and also more stable compared with the absolute count [9,30,37]. Results from the present study are consistent with previous publications [10,30,38], in that WBC count and the NLR were found to be higher in patients with DKA.…”
Section: Discussionsupporting
confidence: 90%
“…This simple ratio, which combines the predictive power of both increased neutrophil and decreased lymphocyte counts, has the advantage of being ubiquitous, cost effective, and also more stable compared with the absolute count [9,30,37]. Results from the present study are consistent with previous publications [10,30,38], in that WBC count and the NLR were found to be higher in patients with DKA.…”
Section: Discussionsupporting
confidence: 90%
“…NLR shows adaptive and innate immune response functions [91][92][93][94]. Several studies have found an increased NLR in patients with DKA [82,[95][96][97]. In a study, the median NLR in patients without ketoacidosis was 1.11; 0.80-1.80.…”
Section: Neutrophil-to-lymphocyte Ratio (Nlr) In Dka Patientsmentioning
confidence: 99%